Barium‐Catalysed Dehydrocoupling of Hydrosilanes and Borinic Acids: A Mechanistic Insight. Issue 16 (25th February 2020) - Le Coz, Erwann; Zhang, Ziyun; Roisnel, Thierry; Cavallo, Luigi; Falivene, Laura; Carpentier, Jean‐François; Sarazin, Yann
Abstract: Invited for the cover of this issue are the groups of Yann Sarazin at the University of Rennes and Laura Falivene at the King Abdullah University of Science and Technology. The image depicts two barium figures working in tandem to mimic the dinuclear nature of the active species in the catalytic cycle described in the manuscript. Read the full text of the article at 10.1002/chem.201904933 . Abstract : " We show that well‐defined barium‐boryloxide complexes constitute effective catalysts for the controlled, fast, and selective production of borasiloxanes that are valuable precursors to borosilicates and heat/chemical resistant materials ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3535 ff. (DOI: 10.1002/chem.201904933 ).